Monitoring of cerebral oximetry in patients with postural orthostatic tachycardia syndrome. Issue 10 (5th August 2019) - Kharraziha, Isabella; Holm, Hannes; Bachus, Erasmus; Melander, Olle; Sutton, Richard; Fedorowski, Artur; Hamrefors, Viktor
Abstract: Aims : Postural orthostatic tachycardia syndrome (POTS) is a disorder of unknown aetiology characterized by orthostatic intolerance and tachycardia with diverse other symptoms, including neurocognitive deficits. Cerebral oximetry non-invasively measures cerebral tissue saturation (SctO2 ) and has been shown to be informative in syncope evaluation. We aimed to assess SctO2 in POTS patients and those with normal response to orthostatic provocation, relative to haemodynamic parameters and symptoms. Methods and results : Thirty-four patients with POTS (29.1 ± 9.5 years; 26 females) and 34 age-/sex-matched controls with normal head-up tilt tests (HUTs) were included. SctO2 at rest and during HUT were compared between POTS and controls. The relation between SctO2, systolic blood pressure (SBP), and heart rate (HR) during HUT was linearly assessed. SctO2 values were related to dizziness or syncope during HUT. The minimum SctO2 -value during HUT was lower (65.4 ± 5.6 vs. 68.2 ± 4.2%, P = 0.023) and changes in SctO2 from supine to minimum HUT value were more pronounced in POTS patients (−5.7 ± 2.9% vs. −4.3 ± 2.1%, P = 0.028). Decrease in SBP from supine to minimum HUT value ( P = 0.004) and increase in HR from supine to HUT value at 3 min ( P = 0.022) correlated with more pronounced SctO2 decrease in POTS but not controls. SctO2 did not predict syncope or dizziness during HUT. Conclusion : Postural orthostatic tachycardia syndrome patients have lower cerebral tissue saturation during orthostatic provocation compared with those subjects having normal haemodynamic response to tilt. Orthostatic decrease in cerebral saturation only weakly correlates with HR increase and does not predict vasovagal reflex in POTS. Other hitherto unknown factors may affect cerebral tissue saturation in POTS.